Google Scholar v sistemu COBISS.SI - Vehovec, Robert (Organizacija znanja, 2006)
This article introduces the Google Scholar service and the relation between Google Scholar and the COBIB.SI shared bibliographic database.
Keywords: internet; podatkovne zbirke; spletni iskalniki